Oral Fibrous Hyperplasia: Report of Two Cases - Permata-Dewi, Elma N.; Salsabila, Sarah R.; Kristiasih, Ardhian R.; Maulana, Rizqan; Hasan, Cahya Y.; Susanto, Hendri (Odovtos - International Journal of Dental Sciences, 2022)
Oral fibroma or Fibrous hyperplasia is a benign tumor in oral cavity may be found at any sites of oral mucosa with clinical feature as a single mass, soft, sessile or pedunculated, smooth surface, painless with or without inflammation. Due to clinical presentation variation, the histopathology examination may be necessary to obtain definitive diagnosis especially in unidentified causes. This case report aimed to present oral fibrous hyperplasia cases in oral cavity with unknown causes. A 50-year-old and 48-year old women complained single mass on anterior palate and left buccal mucosa, pedunculated, slow progress with soft constancy with history of unidentified causes. The excision was taken for the treatment and histopathology examination with clinical diagnosed by fibroma. The wound completely closed after several weeks after treatment. The conclusion of these two cases report showed that the diagnosis of a single mass in oral cavity with unidentified causes need histopathology examination to have final diagnosis.